POTENSI AIR CUCIAN BERAS SEBAGAI PUPUK ORGANIK PADA TANAMAN SELEDRI (APIUM GRAVEOLENS L.) - Milawati Lalla (Fakultas Pertanian Universitas Ichsan Gorontalo, 2018)
Rice washing water is a waste or waste from households that have not been widely used. The purpose of this research is to analyze the influence of rice washing water on growth and yield of celery plants and to see the potency of rice washing water as organic fertilizer in celery plant.The study was conducted in November 2017 - February 2018. The study was prepared according to a Randomized Block Design with 4 treatments and 4 replications namely A0: control, A1: wash water of first rinse rice, A2: water wash of second rinse rice and A3: water washing rice third rinse.The number of replicates as many as 4 and each there are 2 units of plants so that the total plant observed as many as 32 plants. The results showed that rice washing water had no significant effect on the growth of celery plants. The A3 treatment (third rinse washing water) resulted in more leaves than the other treatments. Rice laundry water is potential for use in celery plants but at a more dilute concentration (third rinse washing water).